FLIPBOOK MODULE AS A PRODUCT FOR DEVELOPMENT OF ANIMAL NETWORK MATERIAL MATERIALS FOR STUDENTS XI CLASS SCHOOL - Yuli Damayanti, Ariska; Sholihah, Mar'atus; Kameluh Agustina, Dwi (JOSAR (Journal of Students Academic Research), 2018)
This research is research and development (R & D). the method used is 4D consisting of 4 stages Define, Design, Develop, and Disseminate or adapted into a 4-P model, namely Defining, Designing, Developing, and Spreading.The results of the validation by the validator were 77.5% in the material aspects and 79.3% in the teaching material aspects, and 74.4% in the language aspects. In accordance with the module eligibility criteria that the Flipbook-based module is appropriate to use. The results of ANACOVA analysis showed the effect of Flipbook module teaching materials on student learning outcomes by 22.3%. Based on the results of these studies it can be concluded that the Flipbook module can be said to be worthy of being used as a learning material to improve student learning outcomes.